IMPLEMENTASI PERENCANAAN STRATEGIS - Martin Amnillah (Jurnal Kependidikan, 2015)
The decision making would always affect some efforts in manifesting the existence of an organization, through activities conducted in delivering services as well as development implementation in the upcoming future. Strategic planning as an attempt of decision making is aimed at clarifying the oriented vision of an organization in creating priority and solving the main problem of organization. Despite the fact that planning strategy provides significant benefits, there are no guarantees that everything will run smoothly. This is because the strategy is merely a conceptual procedure and approach. SWOT as a strategic formula could be regarded as a means of analyzing the environment thoroughly either internal or external analysis.